Development and applications of a real-time quantitative RT-PCR method (QRT-PCR) for BRCA1 mRNA - Kroupis, C.; Stathopoulou,A.; Zygalaki,E.; Ferekidou,L.; Talieri,M.; Lianidou,E.S. (Clin.Biochem., 2005)
OBJECTIVES: To develop a real-time quantitative RT-PCR method for BRCA1 mRNA and then use it for the study of BRCA1 gene expression in human MCF-7 breast cancer cells after their exposure to antineoplastic agents and gamma irradiation. DESIGN AND METHODS: The developed QRT-PCR method is based on the real-time monitoring of a fluorescein-labeled TaqMan probe, specific for BRCA1 mRNA, during PCR in the LightCycler. A BRCA1 PCR amplicon was purified, quantitated and used as a standard of known concentration for the development and analytical evaluation of the assay. The method was applied to study the alteration of BRCA1 gene expression after exposure to taxol, doxorubicin, 5-fluorouracil, etoposide or gamma irradiation in human MCF-7 breast cancer cells. RESULTS: The developed method is quantitative, highly specific for mRNA and highly sensitive (detection limit of 4 BRCA1 copies per mug of total RNA). We observed a reduction of BRCA1 expression for all antineoplastic agents used, while the gamma irradiated MCF-7 cells had an increase of expression with a peak at the 10 Gy dose. CONCLUSIONS: The developed BRCA1 QRT-PCR method is quantitative, highly sensitive and specific. The proposed method is rapid, automated, and cost effective and can be used to study BRCA1 expression in a variety of clinical samples
DA - 20041220 IS - 0009-9120 (Print) IS - 0009-9120 (Linking) LA - eng PT - Journal Article PT - Research Support, Non-U.S. Gov't RN - 0 (Antineoplastic Agents) RN - 0 (BRCA1 Protein) RN - 0 (RNA, Messenger) RN - EC 2.4.2.8 (Hypoxanthine Phosphoribosyltransferase) SB - IM
Keywords: Amino Acid Sequence; analysis; Antineoplastic Agents; Base Sequence; BRCA1 Protein; Breast Neoplasms; Carcinoma; Drug Therapy; Female; Gamma Rays; genetics; Greece; Humans; Hypoxanthine Phosphoribosyltransferase; metabolism; methods; Molecular Sequence Data; Reverse Transcriptase Polymerase Chain Reaction; RNA,Messenger; Tumor Cells,Cultured